2017
DOI: 10.1007/s12028-017-0390-y
|View full text |Cite
|
Sign up to set email alerts
|

Decannulation and Functional Outcome After Tracheostomy in Patients with Severe Stroke (DECAST): A Prospective Observational Study

Abstract: Decannulation was achieved in 59.4% of stroke patients surviving the first 12 months after tracheostomy and was associated with better functional outcome compared to patients without decannulation. Further prospective studies with larger sample sizes are needed to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 30 publications
3
28
0
5
Order By: Relevance
“…In the model, which included age, diagnosis, days until admission to rehabilitation, region, swallowing function, and functional ability after the injury, we found that age in particular and a combination of swallowing function and overall functional ability after the injury were highly associated with time to decannulation. Age as an inverse predictor of decannulation is in line with several previous studies investigating predictors of decannulation in either subjects with acquired brain injury or critically ill subjects in general, 9,10,20,31 and swallowing function has also been reported as a predictor of decannulation. 5,10,20,31 For illustrative purposes, we have presented probability curves for subgroups, to show that the model is able to Decannulation from a cuffed tube: n ¼ 520 subjects.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the model, which included age, diagnosis, days until admission to rehabilitation, region, swallowing function, and functional ability after the injury, we found that age in particular and a combination of swallowing function and overall functional ability after the injury were highly associated with time to decannulation. Age as an inverse predictor of decannulation is in line with several previous studies investigating predictors of decannulation in either subjects with acquired brain injury or critically ill subjects in general, 9,10,20,31 and swallowing function has also been reported as a predictor of decannulation. 5,10,20,31 For illustrative purposes, we have presented probability curves for subgroups, to show that the model is able to Decannulation from a cuffed tube: n ¼ 520 subjects.…”
Section: Discussionsupporting
confidence: 90%
“…Several previous studies have investigated predictors of decannulation in subjects with acquired brain injury. However, many studies are of poor quality (eg, small study populations, or the use of univariate analyses), 4,5,7,8,20,[27][28][29] thus limiting the conclusions that may be drawn from those studies. 30 A few recent studies have investigated the prediction of decannulation in larger study populations of subjects with neurological diseases and acquired brain injury using routinely gathered clinical data and applying multivariable analytical methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the low rate of spontaneous recovery in the control group is compatible with the "Decannulation and Functional Outcome After Tracheostomy in Patients with Severe Stroke" (DECAST) cohort study, where only 26% (14/53) of tracheotomised stroke patients could be decannulated within 3 months of stroke. 17 The relationship between treatment efficacy and short times to treatment is presumably related to the development of critical illness dysphagia due to critical illness polyneuropathy and myopathy in patients with prolonged ICU treatment and mechanical ventilation. 33,34 Apart from stroke-related impairment of the central swallowing network, polyneuropathy and myopathy will damage swallowing related cranial nerves and muscles, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In stroke patients, severe dysphagia with related insufficient airway protection is often the main reason why decannulation cannot be performed even three months post stroke. 12,17 Currently, treatment options for accelerating decannulation are very limited. 1 Pharyngeal electrical stimulation (PES) is a novel technique shown to enhance reorganisation of the swallow-related motor-cortex, facilitate activation of cortico-bulbar pathways, and increases salivary substance P levels, a swallow-related neurotransmitter.…”
Section: Introductionmentioning
confidence: 99%